Optimization of the separation conditions of antioxidant peptides from red tilapia (Oreochromis spp.) viscera on cross-flow filtration ceramic membranes (2023)
ABSTRACT: The enzymatic hydrolysate of red tilapia (Oreochromis spp.) viscera was fractionated by means of ceramic tubular membranes with a molecular weight of 3 kDa. For this purpose, a cross-flow filtration system operating with a positive displacement pump was designed, while in order to optimize the process, response surface methodology was used to evaluate the effect of pH, transmembrane pressure (TMP) and feed flow rate on volume reduction factor (VRF), fouling resistances and transmission of antioxidant peptides in the permeate. According to the results obtained, the permeate flow yield was affected at acidic pH with a significant decrease due to membrane fouling. The polynomial models were optimized to find the best combination of response variables, indicating that the following are the optimum operating conditions: pH 8.39, 5 bar and 400 L/h. In addition, an increase in the antioxidant capacity of the permeate was obtained, enhancing the biological activity and indicating its possible use as a nutraceutical.